URGENSI PENDIDIKAN TAUHID DALAM PEMBENTUKAN KARAKTER GENERASI ISLAMI DI ERA GLOBALISASI - Bayu Bambang Nurfauji; Syafriyani; Yeyet Sari Mustika; Ajeng Susanti; Latif Syah Maulana; Nindya Aprilianti (CV. ADIBA AISHA AMIRA, 2026)
Tauhid education plays a crucial role in Islamic education, as it serves as the primary foundation for shaping students' character and personality. Tauhid is not merely understood as a theological aspect, but also as a value that guides individuals' thought patterns, attitudes, and behaviors in daily life. In the current era of massive globalization, Tauhid education and Islamic character education are interconnected. Given that globalization erodes individual moral and spiritual values, this study aims to analyze the role and contribution of Tauhid education in strengthening Islamic character education, as well as how the process of internalizing Tauhid values ​​can shape a young generation with noble character. The research method used is a literature review with qualitative descriptive analysis techniques. Using various sources from books, national journals, and international journals. The results of the study indicate that Tauhid education serves as a moral and spiritual foundation, capable of fostering awareness of the kappa of Allah SWT, an attitude of responsibility, honesty, discipline, sincerity, and social concern. Thus, Tauhid education needs to be implemented comprehensively in all aspects of education to create a generation that is not only intellectually intelligent but also spiritually intelligent